High expression of cuproptosis-related SLC31A1 gene in relation to unfavorable outcome and deregulated immune cell infiltration in breast cancer: an analysis based on public databases - Linrong Li; Lin Li; Qiang Sun (BMC Bioinformatics, 2022)
Abstract Cuproptosis induction represents a promising alternative for immunotherapies and targeted therapies in breast cancer. This study aimed to investigate the prognostic and biological significance of cuproptosis-related genes in breast cancer. In the current study, we examined the transcriptional and clinical data of 13 cuproptosis-related genes in patients with breast cancer from TCGA database. We found that genes DLAT, SLC31A1, ATP7A and ATP7B were significantly related to the overall survival (OS) of breast cancer patients in univariate Cox regression analysis. Unlike lung or kidney cancers, SLC31A1 expression was upregulated in breast cancer samples compared with normal tissues, and predicted poor prognosis. Univariate and multivariate Cox regression analyses indicated that high SLC31A1 level was an independent prognostic factor for shorter OS. A nomogram integrating SLC31A1, age, T-, N-stage and clinical stage was constructed, and the calibration curves of the 1-, 3-, 5-, 10-year OS fitted well with the ideal model. Furthermore, we found that high SLC31A1 expression was related to deregulated immune response and metabolic pathways. Low SLC31A1 level predicted sensitivity to CTLA4 inhibitors but poor response to paclitaxel. Our study may provide novel insights for copper homeostasis and cuproptosis in breast cancer.